2012
DOI: 10.1088/0029-5515/52/10/103006
|View full text |Cite
|
Sign up to set email alerts
|

Outer divertor of ASDEX Upgrade in low-density L-mode discharges in forward and reversed magnetic field: I. Comparison between measured plasma conditions and SOLPS5.0 code calculations

Abstract: Abstract. The scrape-off layer and divertor plasma conditions have been carefully analysed in dedicated ASDEX Upgrade experiments consisting of lowdensity L-mode discharges, with both forward and reversed toroidal magnetic field and plasma current. In forward field, the outer divertor plasma is in a lowrecycling regime with peak target temperature above 25 eV. In reversed field with similar main plasma parameters, the target temperature is below 15 eV and the density is 5 times as high as in forward field, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 35 publications
4
58
0
Order By: Relevance
“…Thus, the combination of both, the Γ dr Θ flow in the PF and the Γ dr r flow brings more plasma to the inner divertor in forward field and to the outer divertor in reversed field. It was further shown at ASDEX Upgrade that the E × B drifts have to be taken into account in order to simulate low density attached divertor plasmas correctly [39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the combination of both, the Γ dr Θ flow in the PF and the Γ dr r flow brings more plasma to the inner divertor in forward field and to the outer divertor in reversed field. It was further shown at ASDEX Upgrade that the E × B drifts have to be taken into account in order to simulate low density attached divertor plasmas correctly [39].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that introduction of the drifts in the plasma transport equations allows us to reproduce quantitatively the divertor asymmetry observed on JET and ASDEX Upgrade (e.g. Aho-Mantila et al 2017;Reimold et al 2017).…”
Section: Modelling Of High-recycling and Detached Divertor Regimesmentioning
confidence: 99%
“…Anomalous transport was described by radially varying transport coefficients which, together with the upstream separatrix density, were adjusted to achieve the best possible agreement with the measured low-recycling conditions in the outer divertor, in the absence of seeding (similar to [6,7]). Simultaneously, agreement with the measured temperature and density profiles at the outer midplane was requested (within measurement uncertainties), yielding high-recycling inner divertor conditions in the simulations, with density a factor of 2 higher than in the ASDEX Upgrade experiment.…”
Section: Solps50 Simulationsmentioning
confidence: 99%
“…The studies focus on two all-metal divertor tokamaks, ASDEX Upgrade and JET, and on low-density L-mode plasmas, in which at least one of the divertor legs is in a low-recycling regime. In the full-W ASDEX Upgrade, a good consistency between various divertor diagnostics has been observed for such conditions in the absence of seeding [6,7], suggesting that these divertor conditions are simple enough to be reproduced by the fluid code packages. The experimental results from N 2 seeded discharges are discussed in Section 2, followed by first qualitative modelling studies in Section 3.…”
Section: Introductionmentioning
confidence: 99%